The Character Education Strategy of SD N Butuh Temanggung Students of Broken Home Victims by Maximizing the Role of Families and Teachers - Ahmad Nur Rohim; Evi Kurniawati (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2021)
This study aims to describe the observations about how the strategies of SD N Butuh Temanggung in developing the character of students who are victims of broken home through collaboration between families and teachers. The social behavior of students who are victims of broken home in SD N Butuh Temanggung is interesting to explore because of the social behavior of students such as violating school rules, opposing, being lazy to go to school or skipping school, lazy to study, lack of enthusiasm for learning, harsh talk, and likes to disturb friends and teachers. The data analysis technique is the triangulation technique, where the data that has been collected is summarized and reduced then its validity is checked. This study uses a qualitative descriptive approach. Data collection techniques by means of interviews and observations. The results showed that in implementing character education for children of broken home victims at SD N Butuh Temanggung, it was carried out through (1) instilling the values of the school's vision and mission in their daily activities; (2) creating a character education program; (3) establishing school rules and class rules; (4) applying religious and ethical values; (5) monitoring the disciplinary behavior of students at home through a daily activity log; (6) involving families and parents in children's character education activities; dan (7) involving the school committee.